Hydrochemical Characteristics and Seasonal Variations of Al-Hammar Marsh, Southern Iraq - Al-Lafta , Hadi Salim; Abdulhussein, Firas Mudhafar (Iraqi Journal of Science, 2022)
Devastated by the combined impact of massive drainage works and upstream damming since the 1980's, Al-Hammar Marsh, Southern Iraq, has completely collapsed with 94 % of its land cover transformed into bare land and salt crusts by 2000. After a policy initiated to restore the Iraqi marshes again in 2003, the marsh recovered about half of its former area. As a part of the ecological recovery assessment of this newly inundated marsh, it is important to investigate the extend impact of desiccation after 3 years of inundation on water quality as the latter plays an important role in the restoration process of the marshes. Therefore, from a restoration point of view, major and trace element distribution and sourcing as well as seasonal variations were studied in the re-flooded marsh of Al-Hammar. First, the Canadian Council of Ministers of the Environment Water Quality Index [1] analyses applied revealed threatened or impaired water quality and conditions in the marsh that depart from natural or desirable levels. Second, multivariate statistical techniques such as Agglomerative Hierarchal Cluster Analyses (AHCA) that were used to analyze the data and identify the possible sources of water pollution in the marsh indicated that some elements such as Ca, SO4, Mg, TDS, Cl, Na, Co, and Ni are associated with natural sourcing while other elements such as Cd, Zn, Pb, and turbidity indicated a possible anthropogenic sourcing. Third, seasonal variations investigation displayed that the water quality is affected by natural seasonal processes such as evaporation and rainfall as well as biological activities. Dry season exhibited an increase in TDS, Ca, Mg, Na, Cl, SO4, and Cd due to the concentration by evaporation during the season compared to the dilution by rainfall during the wet season. In contrast, BOD and DO levels showed a considerable decrease in dry season owing to the poor water ability to hold oxygen at high temperature as a result of higher rate of microbial metabolism.